A Hybrid Approach to Teamwork - Trigo, Paulo; Coelho, Helder (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2007)
In the aftermath of a large-scale disaster, agents’ decisions derive from self-interested (e.g. survival), common-good (e.g. victims’ rescue) and teamwork (e.g. fire extinction) motivations. However, decision-theoretic models find it difficult to incorporate motivations, and mental-state models find it difficult to deal with uncertainty. We present an hybrid, CvI-JI, approach that combines: i) collective ‘versus’ individual (CvI) decisions, founded on the Markov decision process (MDP) quantitative evaluation of joint-actions, and ii) joint-intentions (JI) formulation of teamwork, founded on the belief-desire-intention (BDI) architecture of general mental-state based reasoning. Experiments show the CvI-JI performance’s improvement during a policy learning process.